Climate and Environmental Policy in Indonesia: Challenges and Opportunities - Sunarya, Amud (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Climate and environmental policy issues are increasingly pressing in the global context. This requires policies that mitigate and adapt to climate change, which is influenced by factors such as rising global temperatures, extreme rainfall and severe natural disasters. The purpose of writing this article is to review various theoretical foundations relevant to climate policy, including the impact of climate change on various sectors, the role of greenhouse gases in global warming, the concept of climate justice, and the importance of adaptation and mitigation strategies. Apart from that, this article also aims to discuss the importance of international regulations such as the Kyoto Protocol and the Paris Agreement, the role of environmental economics in policy making, and political dynamics that influence climate policy. This research uses a literature review method to evaluate previous research on climate and environmental policy by utilizing sources such as Publish or Perish. From the results of a search on Scopus with the keywords "climate and environmental policy," 297 articles were found, and after filtering, ten articles exploring various aspects of climate and environmental policy were identified. Qualitative data processing is carried out in three stages: data reduction, data presentation, and conclusion. Data reduction involves selecting data that needs to be coded, sharpening the data, and eliminating unnecessary data. Data presentation is carried out through narrative text to facilitate understanding, while inference uses deductive techniques, drawing conclusions from general to specific data. The results of this literature review emphasize the need for a holistic approach that integrates mitigation and adaptation efforts, addresses economic and social impacts, monitors the implementation of international policies, actively involves stakeholders, and focuses on sustainable development. This report highlights the importance of public education and awareness in supporting sustainable policy implementation and behavior change.